Time limit at VO2max velocity in elite crawl swimmers - Ricardo Fernandes (2008)
he purpose of this study is to assess, with elite crawl swimmers, the time limit at the minimum velocity corresponding to maximal oxygen consumption (TLim-vVO2max), and to characterize its main determinants. Eight subjects performed an incremental test for vVO2max assessment and, forty-eight hours later, an all-out swim at vVO2max until exhaustion. VO2 was directly measured using a telemetric portable gas analyzer and a visual pacer was used to help the swimmers keeping the predetermined velocities. Blood lactate concentrations, heart rate and stroke parameter values were also measured. TLim-vVO2max and vVO2max, averaged, respectively, 243.2 +/- 30.5 s and 1.45 +/- 0.08 m . s (-1). TLim-vVO2max correlated positively with VO2 slow component (r = 0.76, p < 0.05). Negative correlations were found between TLim-vVO2max and body surface area (r = - 0.80) and delta lactate (r = - 0.69) (p < 0.05), and with vVO2max (r = - 0.63), v corresponding to anaerobic threshold (r = - 0.78) and the energy cost corresponding to vVO2max (r = - 0.62) (p < 0.10). No correlations were observed between TLim-vVO2max and stroking parameters. This study confirmed the tendency to TLim-vVO2max be lower in the swimmers who presented higher vVO2max and vAnT, possibly explained by their higher surface area, energy cost and anaerobic rate. Additionally, O2SC seems to be a determinant of TLim-vVO2max.